Memorandum of a journal, kept daily during the last march of Jefferson Davis - Campbell, Given
"Memorandum of a journal, kept daily during the last march of Jefferson Davis." Describes the flight of Jefferson Davis and his cabinet from Greensboro, N.C., to Irwinville, Ga., where Davis was captured by Federal troops.
Microfilm of typewritten transcript.
Positive photocopy of typewritten transcript.
Private.
Confederate army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Davis, Jefferson, -- 1808-1889.; Confederate States of America. -- Army -- Officers; Confederate States of America; United States -- History -- Civil War, 1861-1865.; Army officers, Confederate